Investigation of a Dissipating Mesospheric Bore Using Airglow Imager and Direct Numerical Simulation. Issue 4 (22nd April 2023) - Ramachandran, Kesava; Sivakandan, Mani; Chau, Jorge L.; Urco, Juan M.; Gerding, Michael; Grundmann, Sven; Smith, Steven M.
Abstract: Atmospheric gravity waves play an important role in driving the dynamics of the Mesosphere and Lower Thermosphere and the basic structure of this region is determined by momentum deposition of these waves. Mesospheric bores are a type of non‐linear response that cause the amplification of gravity wave, due to trapping, that is characterized by a propagating step‐like jump followed by undulating waves. They require a stable layer or duct to travel horizontally with little attenuation thereby capable of transporting wave energy and momentum over larger distances. We present a prominent bright undular bore event observed in the mesospheric O( 1 S), O2, and OH emission layers on 16 March 2021 over Germany. A striking feature of this observation is the capture of bore's rapid dissipation around the center of the imager's field of view. The vertical temperature profile obtained from the satellite data indicates the presence of temperature inversion layer which acted as a thermal duct for the bore propagation. In addition, we have performed idealized two dimensional direct numerical simulations (DNS) of Navier‐Stokes equations under Boussinesq approximation. The DNS results reproduce many important characteristics of the observed airglow event like the nonlinear wave‐steepening, number of trailing waves, and its dissipation by implementing a thermal duct and a wave‐like perturbation. Furthermore, the DNS results also indicate that the duct width and amplitude of the initial perturbation have a considerable effect on the bore morphology. Key Points: Observation of a mesospheric bright bore event that dissipated within the field of view The duct that enabled the bore propagation was near the O( 1 S) emission layer based on the observational data The majority of the observed features are reproduced with idealized 2D direct numerical simulations using Boussinesq approximation